THE EFFECTIVENESS OF USING AUTHENTIC MATERIALS IN TEACHING ENGLISH AS A SECOND LANGUAGE - Sri Rahayu (Jurnal Scientia, 2023)
The issue of using authentic materials in language classes has been influential for the last two decades. Additionally, many practitioners involved in foreign language teaching and research argue about the benefits of using authentic materials. These benefits can range from highlighting understanding, presenting real language, providing opportunities to introduce cultural issues, to increasing motivation, and creating language awareness. However, the use of authentic materials in learning contexts such as ESP (English for Specific Purposes) as a way to make English a second language has always been controversial. In this case, this research aims to review the application of the material in the ESP context. In order to achieve this goal, there will be a review of authenticity and authentic materials in comparison with textbook-based materials focusing on quality traits and features as well as approaches that encourage the use of authentic materials such as communicative language teaching. The research method used was descriptive qualitative with a literature study approach. This research will investigate the motivational nature of the material for ESP learners with the assumption that the language is used as a second language. This research presents several guidelines for selecting and teaching reading materials in ESP courses in English language learning.